Implementation of Mudik Ied Al-Fitr 1443 H Regulation: Security, Safety, and Comfortable Mudik From Maqashid Al-Sharia Perspective - Tri Wahyu Hidayati (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2023)
This article aims to show the government's efforts to realize the benefit of mudik (homecoming) travelers on the Eid al-Fitr 1443 H. The regulations issued by the government to realize the benefit are a manifestation of one of the values of Maqashid al-Sharia. The maintenance of religion, soul, mind, property, and offspring is highly considered in the rules set by the government to realize homecoming safety, security, health, and comfort. Homecoming this year feels very different from the previous year. This year it is allowed to go home after two years of being banned to prevent the spread of Covid 19, which is very fast and dangerous. This research was conducted by analyzing the homecoming rules set by the government and the results of observations on the implementation of Eid al-Fitr 1443 H homecoming from print and electronic media. The results of this research are significant as input for the government to establish legal provisions to realize the benefit of the community. In comparison, residents must also obey the rules set as long as they do not conflict with religious principles.